Synergistic effects of beneficial microbial inoculants and SMS-amendments on improving soil properties and Pinus seedling growth in degraded soils - Bo, Xuan; Liu, Yong; Zhang, Hong; Su, Chao; Miao, Yang (Frontiers in Microbiology, 2025)
Spent mushroom substrate (SMS) is a promising organic amendment for remediating degraded soils, yet its effectiveness is often limited by poor compost maturity and stability. This study aimed to enhance the quality and functionality of SMS compost through microbial inoculation and to evaluate its impact on soil improvement and plant growth. Three plant growth-promoting strains [Bacillus subtilis (B. subtilis), Azotobacter chroococcum (A. chroococcum), and Paenibacillus mucilaginosus (P. mucilaginosus)] and their combination as a mixed microbial inoculant (MMI) were used in composting. Subsequent pot experiments assessed changes in soil physicochemical properties, nutrient levels, microbial diversity, and the growth of Pinus sylvestris seedlings. Results showed that SMS amended with MMI significantly improved soil porosity, pH, and nutrient content, while enriching beneficial microbial communities dominated by Proteobacteria and Basidiomycota. Moreover, MMI treatment notably enhanced plant height, stem diameter, and chlorophyll content compared to control treatments. These findings highlight the synergistic effect of mixed microbial inoculants in optimizing SMS compost and promoting soil and plant health. The approach offers a sustainable strategy for the circular reuse of agricultural waste and effective restoration of degraded soils.